Hubungan Beban Kerja Dengan Stres Kerja Dosen di STIKes Senior Medan - Agustinus Manullang; Faadhil Faadhil (Universitas Medan Area, 2023)
This study aims to determine the relationship between workload and work stress for Senior STIKes Medan lecturers. The method in this study uses quantitative methods. The population in this study were Senior STIKes Medan lecturers. The sample in the study amounted to 60 people. The sampling technique uses total sampling. The data collection method uses a workload scale and work stress scale with a Likert Scale model. Data analysis method using Person Product Moment. The results of this study indicate that there is a positive and significant relationship between workload and work stress (r = 0.448, p = 0.000). Thus the hypothesis in this study is accepted.